2009
DOI: 10.1007/s00464-008-0286-1
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of endoscopic ultrasound-defined pleural, pericardial or peritoneal fluid in oesophageal cancer

Abstract: EDFE was an important adverse prognostic indicator, but patients deemed to have operable tumours should still be treated with radical intent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…56 Twine et al found it to be present on endoscopic ultrasound (EUS) in 16.3% of patients diagnosed with esophageal cancer, with a pericardial effusion associated with lower survival rates. 57 Prompt drainage via pericardiocentesis or surgery is indicated in patients with clinical tamponade or purulent pericarditis. 58 Rarely, the latter conditions may occur secondary to an esophagopericardial fistula due to esophageal malignancy.…”
Section: Esophagopericardial Fistula and Pericardial Effusionsmentioning
confidence: 99%
“…56 Twine et al found it to be present on endoscopic ultrasound (EUS) in 16.3% of patients diagnosed with esophageal cancer, with a pericardial effusion associated with lower survival rates. 57 Prompt drainage via pericardiocentesis or surgery is indicated in patients with clinical tamponade or purulent pericarditis. 58 Rarely, the latter conditions may occur secondary to an esophagopericardial fistula due to esophageal malignancy.…”
Section: Esophagopericardial Fistula and Pericardial Effusionsmentioning
confidence: 99%
“…Ungeachtet von Ungenauigkeiten in der Zuordnung individueller T-und N-Stadien [69,72,73] gelingt die prognostisch entscheidende Differenzierung zwischen lokal begrenzten (T1N0, T 2N0) und fortgeschrittenen Karzinomen (≥ T3 und/oder N1 -N3 und/oder M1) endosonografisch mit hoher Sicherheit [69] und erlaubt die Zuordnung zu verschiedenen therapeutischen Kategorien. Die endosonografisch nachgewiesene Anzahl und Lokalisation von Lymphknotenmetastasen [36,38,59] ist ebenso prognostisch relevant wie die endosonografisch gemessene Tumorlänge [36,59], das aus Tumorlänge und maximaler Tumordicke errechnete Tumorvolumen [58] und der Nachweis von kleinen pleuralen, perikardialen und peritonealen Flüssigkeitsansammlungen [74]. Mehrere Studien haben aufzeigen können, dass das endosonografische Staging wahrscheinlich durch Verbesserung stadienadaptierter Therapieentscheidungen die Prognose der untersuchten Patienten positiv beeinflusst [38,53,75] und kosteneffektiv ist [76].…”
Section: öSophaguskarzinomunclassified
“…2 The evolution of an open Heller myotomy to the laparoscopic approach has led many gastroenterologists to consider surgery as the first treatment option. 6 Pascricha et al 5 used this technique successfully to perform endoscopic myotomy in a porcine model. 3 Other endoscopic approaches have been described.…”
Section: Mineola New York Usamentioning
confidence: 99%